A clinical systematic literature review of treatments among patients with advanced and/or metastatic human epidermal growth factor receptor 2 positive breast cancer - Kerigo Ndirangu; Rachel Goldgrub; Vanita Tongbram; Rajee Anton; Bagrat Lalayan; Joyce O'Shaughnessy; Sarah E Schellhorn (Becaris Publishing Limited, 2024)
Aim: This systematic literature review aims to summarize the efficacy/effectiveness of treatments, including eribulin (ERI)-based and anti-human epidermal growth factor receptor 2 (HER2) treatments in advanced/metastatic HER2+ breast cancer. Methods: Three databases from 2016 to September 2021 were searched for clinical trials and observational studies in patients receiving first-line (1L) standard of care (SOC), second-line (2L) SOC or third-line or subsequent lines (3L+). Results: 2692 citations were screened, and 38 studies were included. Eleven studies were randomized-controlled trials (RCTs; 5 in 1L, 6 in 3L+), 6 were single-arm trials (5 in 1L, 1 in 3L+) and 21 were observational studies (13 in 1L, 6 in 2L, 4 in 3L+ [note that studies with subgroups for 1L, 2L, 3L+ are double-counted]). Longer overall survival (OS) was associated with 1L and 2L treatment, and for 3L+ studies that included ERI, ERI or trastuzumab (Tmab) + ERI led to longer OS than treatments of physician's choice (median OS of 11, 10 and 8.9 months, respectively). Progression-free survival was 9 months in Tmab + pertuzumab (Pmab) + ERI, 4 months in Tmab + ERI and 3.3 months in ERI. Conclusion: Available treatments provide a wide range of efficacy. However, later lines lack standardization and conclusions on comparative effectiveness are limited by differing trial designs. Thus, the chance of prolonged survival with new agents warrants further research.